The status of Saudi measures of deprivation: A review with policy recommendations on a missing indicator in Saudi epidemiologic research - Reem S. AlOmar (Journal of Family and Community Medicine)
Abstract: In epidemiology and public health, social determinants of health are an important concept, where deprivation plays a central role in the overall health status. This paper reviews the literature on deprivation and health, as well as reviews the role deprivation plays in the field of epidemiology and finally focuses on the Saudi context and provides recommendations for policymakers. This narrative review consisted of a literature search in MEDLINE, CINAHL, and PsychInfo. Search terms included key concepts of “measures of deprivation” and “epidemiology”. Epidemiologists have found that health is socioeconomically patterned and follows a social gradient so that the more deprived an individual is, the poorer their health. In the United Kingdom, epidemiologists have been able to compute composite indices for deprivation and periodically update and link them to national databases. A composite index provides an overview of the ranking of deprivation and epidemiologically, provide parsimonious models rather than analyzing several separate variables. In Saudi Arabia, only two indices were published in 2018 with census data from 2004. Consequently, epidemiologists and researchers have difficulty utilizing this outdated index and incorporate it into national emerging databases. Recommendations provided in this paper include facilitating epidemiologists’ accessibility to the data on the 2022 census, especially at smaller geographical levels to enable them to compute small area level-based measures of deprivation (MoD). Also, to utilize the recent technological advances to enable data linkage between the different databases and encourage the adoption and incorporation of the MoD into national databases and public health programs.